Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 3265437 species occurrences available in GBIF matching the query: null The dataset includes 3265437 records from 26308 constituent datasets: 371 records from Bannwald Burghauser Forst. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 9 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 1778 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 80 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2812 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 517 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 10654 records from Bryophyte specimens of The Nagoya University Museum. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 34520 records from University of Guam Insect Collection. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 832 records from Benthic foraminifera and algae abundance of Hole 81-552A. 1530 records from Pollen record of sediment core Bokanjacko Blato 1. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 395 records from Planktic foraminifera abundance of Hole 32-310. 26 records from Dinoflagellate abundance of Hole 81-554. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 140 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 109 records from Nannofossil abundance of Hole 24-232. 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 211 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 5 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 33 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 1189 records from UWIZM Molluscs. 1 records from Oribates fusifer. 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 5514 records from MCP-Aves - Coleção de Aves. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 265 records from Nannofossil abundance of Hole 36-329. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 75 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 988 records from flower availability 2008 Alb-korrigiert. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 13 records from Dinoflagellate abundance of Hole 14-144. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 121231 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 29 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 488 records from Planktic foraminifera distribution of sediment core SU81-07. 235 records from Range table from benthic foraminifers in ODP Hole 161-974B. 2 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 1645 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 1158 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 14 records from Benthic foraminifera abundance of Hole 96-620. 86676 records from Marine Offshore Seabed Survey data held by JNCC. 100 records from Nanoplankton abundance at station GeoB2006-4. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 1626 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 18 records from Naturtag. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 406575 records from Herbarium of Taiwan Forestry Research Institute. 93 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 23 records from Ackerrain Plönhagen. 607514 records from Plant. 258 records from Malawi-Histeridae-Biodiversity-Data. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1438 records from Planktic foraminifera abundance of Hole 7-64. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 85 records from (Fig. 4) Nannofossil abundance of Cretaceous profile Pré-Guittard, SE France. 120 records from Total foraminifera counts of multinet M21/2_MSN650. 12859 records from Colecção Entomológica IIA. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 17155 records from MZFC/Coleccion de Aves. 1 records from Oribates calcaratus. 214 records from Total foraminifera counts of multinet M21/1_MSN608. 490387 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 6613 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 7123 records from DMNS Egg Collection (Arctos). 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 2326 records from Jardín Botánico Atlántico, Gijón: JBAG. 26 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 164357 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 128 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 238 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 69 records from BIRDRACE Pfeifenten. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 1432 records from Phytoplankton abundance in surface water during cruise CD61. 6158 records from Marine metagenome ICM_JRV. 29 records from Total foraminifera counts of trap L3_92_45. 374 records from Medicinal potential of African plants (Togo). 91 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 322 records from Collections ichtyologiques et herpétologiques (BOUM). 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 10738 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 125055 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 278 records from MfN - Fossil invertebrates IIa. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 308 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 191 records from sediment microorganism Metagenome. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 6192 records from NE Scotland fish records 1800-2010. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 251 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 13269 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 7 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 270 records from bmhs_weatherheadshell_collection. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 220 records from Living Cirripedia. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 2 records from Contributions to the palaeofauna of Ptinidae (Coleptera) known from Baltic amber. 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 173415 records from Hymenoptera specimen database of Kyushu University. 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 774949 records from Finnish Floristic Database (Literature Sources). 174 records from The Myriapoda Collection of the National Museum of Nature and Science. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 3755 records from Données naturalistes de Charlotte PICARD. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 6652 records from Inventory of plant species through Benin (West Africa). 509 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 4109 records from South Caribbean Diversity. 6192 records from marine sediment metagenome Metagenome. 561 records from Range table from benthic foraminifers in ODP Hole 146-889A. 3 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 5 records from Ostracoda abundance of Hole 44-390. 72185 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 1773 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 7 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 26111 records from University of California Santa Barbara Invertebrate Zoology Collection. 285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 11630024 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 175 records from Nannofossil abundance of Hole 41-366A. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 3 records from А new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 6390 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 6 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 136 records from Nannofossil abundance of Hole 39-359. 116480 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 31 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 71 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 3 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 80 records from An updated checklist of Iranian Encyrtidae (Hymenoptera, Chalcidoidea). 105857 records from Fish specimens of Kagoshima University Museum. 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 13647 records from UTEP Invertebrates (Arctos). 152 records from Nannofossil abundance of Hole 49-412. 26 records from Abundance of benthos infauna at station PS1240-1. 4 records from A new species of Lamprodila (Ovalisia Kerremans, 1900) (Coleoptera: Buprestidae) from Sulawesi, Indonesia. 611 records from Données du Râle gris sur le territoire de la Guadeloupe. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 163 records from Relative abundance of coccosphere-units at site GIK23414. 35 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 995 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 3621 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 21 records from Nannofossil abundance of Hole 3-22. 828 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 20 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 1305 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 3063 records from Données entomologiques sur la Réserve Naturelle de l’Étang Noir. (Seignosse, Landes). Bilan des études 2001 à 2009. 89 records from A review of the genus Potemnemus Thomson, 1864 (Coleoptera: Cerambycidae) with description of a new species from Papua New Guinea. 53 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 3148 records from Ross A. Layberry, Collection. 348 records from Antarctic pycnogonids. 62776 records from MLZ Bird Collection (Arctos). 74 records from Birdrace_Gätkes_Schergen-Helgoland. 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 1212 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 119 records from Microfossil abundance of Hole 50-416A. 3 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 24 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 356 records from UWYMV Herpetology Collection (Arctos). 160 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 14069 records from Midden-Limburg Fish Ponds Survey. 732 records from DSMZ Collection of Plant Viruses. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 105706 records from Herbarium Senckenbergianum (FR) - Fungi. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 170 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 8 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 451 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 5908 records from Colecção Entomológica do Museu de História Natural de Maputo. 177 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 209 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 18 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 724 records from Heritage Trees of Ireland. 613 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 42 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 2215 records from Collection Polychaeta - ZSRO. 15680 records from imr_mareano_rpsledge. 1383 records from Plant observations from Białowieża National Park. 5406 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 85277 records from University of Ghana - Ghana Herbarium. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 17 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 182 records from Nannofossil abundance of Hole 55-433. 8 records from RISC Non-Native Species Records for Zebra Mussel. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 1911 records from Pollen profile RAC20, Lake Racou, France. 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 132 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 21 records from Characterization of Microbial Community Structure and Population Dynamics of Tetrachloroethene-Dechlorinating Tidal Mudflat Communities using a Multipronged Approach. 10898 records from Inventario de Hymenóptera; parasítica en México. 23 records from Abundance of benthos infauna at station GIK23055-1. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 10 records from Benthic macrofauna abundance of sediment core 13200-017. 1798 records from 3Soil16S. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 4201 records from Gunma Museum of Natural History, Fungi Specimen. 13979 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 68 records from Nannofossil abundance of Hole 24-233A. 2532 records from Microbial community diversity in Arctic marine sediments and Planktonic microbial. 1057 records from Palynological analysis of sediment core GeoB9508-5. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 6 records from Abundance of benthos infauna at station GIK23065-1. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1618 records from uncultured eukaryote Raw sequence reads. 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 593 records from Flux data of NU2_trap (Table A1). 4 records from Planktic foraminifera abundance of Hole 17-166. 238 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 2710188 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 228 records from Bishop's University Insect Collection (BUIC). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 24 records from ALTERECO_2017_12_18. 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 5350 records from Sediment metagenome. 1702 records from BioGIS - Bryophytes - HUJ collections. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15278 records from Anymals+plants - Citizen Science Data. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 5494 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 71494 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 2208 records from marine sediment metagenome Raw sequence reads. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 462 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba. 2443 records from Cnidaria MZS. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 423 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 4816 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 243 records from Thistles species and abundance. 6 records from Mammalia (JNHM-MM). 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 13942 records from The Vascular Plants Collection of the University of Goettingen. 2120 records from Flora vascular acuática de la cuenca del Río Tamesí. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 755529 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 1 records from Larval morphology of Plagiosterna adamsii (Baly) and P. aenea (Linnaeus) with resurrection of Gastrolinoides Chûjô & Kimoto and P. formosana (Bates) (Coleoptera: Chrysomelidae: Chrysomelinae). 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 120 records from BIRDRACE The early birds. 9 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 92 records from Protozoa Abundance_Microbial Parameters. 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 1125 records from Données naturalistes de Stéphane ORIO. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 182790 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 55 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 665 records from Collection Echinodermata - ZMB. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 244 records from WildesMoor bei Schwabstedt. 443 records from Inventario herpetofaunístico del noroeste de Hidalgo. 391 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 3714 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 115 records from Antarctic Pycnogonids II. 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 6979 records from Upper Silesian Museum, Bird Observations. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 234 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 150 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 223 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 126 records from SEWBReC Springtails and allies (South East Wales). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 38509 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 13110 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 425 records from Percentages of planktonic foraminifera species in sediment core V22-38. 55 records from Dinoflagellate abundance of Hole 28-274. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 27 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 50 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 23138 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 1 records from A new brachypterous Filchneria and two new generic records for China, Arcynopteryx and Pictetiella (Plecoptera: Perlodidae). 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 495 records from Planktic foraminifera counts of sediment core A15-558. 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 19 records from Données naturalistes de LE GLOANEC Vincent. 57451 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5. 370 records from Size of planktic foraminifera at CTD station PS55/051. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 3 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 5 records from Revision of Chimarrogale (Lipotyphla: Soricidae) from Vietnam with comments on taxonomy and biogeography of Asiatic water shrews. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 4479 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 11 records from New records of deep-sea shrimps of family Solenoceridae Wood-Mason & Alcock, 1891 (Crustacea: Decapoda: Dendrobranchiata) from Southwestern Atlantic. 7122 records from Whale catches in the Southern Ocean. 187017 records from UWFC Ichthyology Collection. 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 279 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 35 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 3145 records from PCE/TCE dechlorinating microbial community and dehalogenase genes from Wonju Stream, South Korea. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 9 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 20 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 85 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 614 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 34332 records from Protist Diversity in the East China Sea. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 18 records from Anfibios presentes en el Cerro Jánano. 1715185 records from NBIS Records to December 2016. 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 27 records from Planktic foraminifera abundance of Hole 51-417B. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 133 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/042-2. 65 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 6255 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 333 records from renaturierter Main (Kemmern bei Bamberg). 353 records from Contribución a la distribución, ecología y estado de conservación de dos especies del género Sceloporus, endémicas de la región del Cabo, Baja California Sur. 13469 records from Montana State University - Billings. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 798 records from Planktic foraminifera abundance of Hole 27-262. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 108313 records from Arizona State University Hasbrouck Insect Collection. 39 records from Planktic foraminifera abundance of Hole 27-260. 447 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 665 records from Geochemistry and sedimentology on core POS200/10_28-1. 3618 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 4 records from Palaeopsylla (Palaeopsylla) aysenurae n. sp., a new ctenophthalmid flea (Siphonaptera: Ctenophthalmidae) from Turkey. 89 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 429 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3587 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 11 records from Barsine wangi, a new species from Guangdong, southern China (Lepidoptera, Erebidae, Arctiinae). 9446 records from Batsites inventory for England (1949-2011). 5340 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 6 records from A new species of salamander of the genus Hynobius (Amphibia, Caudata, Hynobiidae) from South Korea. 59016 records from Isopoda (Interim dataset). 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 1219 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 94 records from Microbes in drinking water and biofilms (18S rDNA amplicon study). 195 records from Plant macrofossil concentrations from an open section of Lac de Fully sediments. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 250796 records from Données du CEN Picardie concernant la Faune, Flore, Fonge. 87901 records from MDFRC macroinvertebrate survey. 10 records from Lectotype designations, taxonomic notes and new synonymy in some species of the bee genus Centris Fabricius, 1804 described by William Henry Fox (Hymenoptera: Apidae). 177 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 3273 records from Algae collection. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 6 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 7 records from Nannofossil abundance of Hole 6-49. 151 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 9476 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 55 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 5 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 5061 records from Metagenome from mudbank Area,Alappuzha Kerala India. 68 records from Planktic foraminifera abundance of Hole 16-161. 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 27545 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 323 records from Eco-Stratégie_2017_12_18. 968 records from Guinea-Bissau Herpetological Collection - IICT. 411 records from SuLaMa reptile survey I 2012. 2 records from Psilotris vantasselli, a new species of goby from the tropical western Atlantic (Teleostei: Gobiidae: Gobiosomatini: Nes subgroup). 61 records from Shrews of Poland. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 9 records from Nannofossil abundance of Hole 2-11. 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 78 records from (Table 3) Downcore distribution of live benthic foraminifera of sediment core SW_2b, California continental borderland. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 908 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 269 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 2274 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 106100 records from Fish (NSMK-PI). 1186 records from Nannofossil abundance of Hole 75-530A. 24 records from Planktic foraminifera abundance of Hole 20-200A. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 3 records from One new species and new record of the leafhopper genus Watara Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 10 records from Collection Myriapoda - SNSD. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 78612 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1357 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 1868 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 3 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 17 records from Marine metagenome ICM_AGW. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3546 records from Dorset SW Pilot species dataset. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 1924 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 882 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 144 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 1 records from On two italian Lithobius species described by Silvestri with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda Lithobiidae). 95 records from Kystfuruskoger i Tysnes og Fusa. 2080 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 91 records from Diatom abundance of Hole 95-613. 8 records from Die Bachspezies 2008/2009. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 5 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 78 records from Geographical and bathymetric distribution of mysids (Crustacea: Mysida) in the seas of the Iberian Peninsula. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 50 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 68 records from Streuobstwiese. 23 records from Abundance of benthos infauna at station GIK23042-2. 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 371 records from Benthic foraminifera and algae abundance of Hole 81-554A. 663 records from Benthic foraminifera counts of sediment core GIK23352-3. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 49 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 1056 records from Diatom assamblage in samples from sediment trap OG4. 2787427 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 363 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 170543 records from England Non Native Species records 1965 to 2017. 134 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 164 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 8 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1513 records from M. Gollop Collection. 3350 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 53207 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from Données naturalistes d'Olivier DELZONS. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 218 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 3178 records from Newfoundland sediment pyrosequencing. 859 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 2 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 4 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 8 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 1123 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 6 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 174 records from BIRDRACE Bon(n)apartemöwen. 18 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 1434 records from Nannofossil abundance of Hole 94-607. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 2171 records from Thrips (Thysanoptera) in Norway. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 2606 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 4065 records from Microbial community in permeable intertidal sediment. 69 records from Entdeckertour am Muldestausee 1/05. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 541 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae). 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 3 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 160 records from BIOTOPE_2017_12_18. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 108 records from BIRDRACE Diesmal sehen wir mehr. 16 records from Insect Collections of Okomu National Park- Nigeria. 1134 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 412 records from Heinersdorfer Sumpfwiese. 133650 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 291402 records from ARABEL - Arachnologia Belgica. 977 records from Habitat and host related variation in sponge bacterial communities in Indonesian coral reefs and marine lakes. 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 36 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 1764 records from Arachnida of Costa Rica (INBio). 15 records from Nannofossil abundance of Hole 6-48B. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 3 records from A new species of Schindler's fish (Teleostei: Gobiidae: Schindleria) from the Malay Archipelago (Southeast Asia), with notes on the caudal fin complex of Schindleria. 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 29876 records from European Moth Nights. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 85 records from Planktic foraminifera counts of sediment core V27-47. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 931 records from Données naturalistes de Mathilde DUSACQ. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 8 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 2044 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 1036 records from BUND - Dassower See (Lübeck/Dassow). 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 385 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 54402 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 4 records from Sächsische Schweiz (Wehlener Gebiet). 356 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 40 records from Planktic foraminifera abundance of Hole 14-137. 2406 records from UWYMV Bird Collection (Arctos). 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 42 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 1288808 records from PlutoF platform observations. 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 136 records from Total foraminifera counts of multinet M21/6_MSN784. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 45 records from Nannofossil abundance of Hole 10-89. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 177 records from Nannofossil abundance of Hole 30-285A. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 356 records from Morphologische Daten von Puffinus creatopus. 23648 records from WTSWW Data: All Taxa (West Wales). 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 148 records from Herbarium BSG Hepaticopsida. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 69 records from Unter hellen Zinnen und finsteren Grotten. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 92 records from Nottekanal, Klasse 7 - 10. 597 records from Percentages of planktonic foraminifera species in sediment core V30-40. 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 4845 records from Inventaire des Mollusques Sphaeriidae de France. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3030 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 884 records from Sea shells of New South Wales. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4222 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 50 records from Flora und Fauna im Brexbachtal. 5 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 5710 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 43574 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 38 records from Was lebt in der Brutzwiese?. 2 records from Nannofossil abundance of Hole 4-26A. 96 records from Planktic foraminifera abundance of Hole 22-212. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 287 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 86 records from Données naturalistes de Pierre-Alexis RAULT. 440 records from Wichita State University Collection. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 14 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 647 records from pbzt_insect_biodiversity. 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 281 records from NZCS Upper Tapanahony Expedition 1991. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 1 records from Oppia nitens. 24 records from Tanzanian Vertebrate Collection. 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 3 records from DD_cyano Targeted loci environmental. 603 records from Fossil (NSMK-FO). 20 records from Planktic foraminifera abundance of Hole 19-185. 50 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 2140 records from Captive Primate Specimens of Japan Monkey Centre. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 36 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 12 records from A Catalogue and Historical Study of the Odonata of Ecuador. 4621 records from Códigos de barras de la vida en peces y zooplancton de México. 3 records from A new fossil species of Pycnomerus Erichson (Coleoptera: Zopheridae) from Baltic amber, and a replacement name for a Recent North American congener. 5 records from Loricifera - SMF. 9 records from New records and their associated DNA barcodes of the butterfly family Hesperiidae in Tibet, China. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 243 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 47 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 480819 records from KTP Ring Data. 49 records from Données naturalistes (Rhopalocères et Zygènes) de Bob WHITMARSH (indépendant). 4378 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 187 records from Mollusca specimens of Kuroshio Biological Research Foundation. 24 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 69319 records from Données de l'Observatoire de la Faune de Bourgogne. 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 1560 records from UNM Earth Sciences Collection (Arctos). 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 539 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 150 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 2398 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 5448 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 321 records from Echinoderms from the Seaflower Biosphere Reserve. 55 records from New records of ant species from Yunnan, China. 280 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 281 records from Nannofossil abundance of Hole 22-217. 1 records from First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rondônia, western Amazonia, Brazil. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 218 records from Nannofossil abundance of Hole 49-408. 84 records from Total foraminifera counts of multinet M21/5_MSN728. 11 records from Analyses of the recent components of sediment core PS1011-1. 6402 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 2 records from Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China. 3 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 28 records from MVZ Herp Observations (Arctos). 50 records from Beetles on polypores at 4 sites in Norway. 72 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 1590 records from Relative abundances of twenty-eight dominant benthic foraminifera species of DSDP Hole 23-219 (Table 1s). 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 2599 records from Microbial diversity associated with copepods in the North Atlantic subtropical gyre. 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 10 records from Two new species of Ankareus Kerremans (Coleoptera: Buprestidae: Haplostethinae) from southern Africa. 6 records from Foraminifera abundance of Hole 58-442. 126 records from Amphibians and Reptiles in Selected Sites in Palawan Province, the Philippines. 11 records from Dysaphis (Dysaphis) kadyrovi sp. nov. — a new aphid species (Hemiptera: Aphididae) from Tajikistan. 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 11258 records from Uncultured eukaryotes Targeted Locus (Loci). 700 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 157 records from BIRDRACE Rheinische Wasserrallen. 1662 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 407 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 98 records from Warnowtal (Rostock). 12 records from A systematic appraisal of the types of ten species of Otostigmus (Parotostigmus) (Scolopendromorpha, Scolopendridae, Otostigminae). 3 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 1576 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2747 records from Données naturalistes de David HAPPE. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 8 records from A taxonomic review of the genus Dicranorhina Shuckard (Hymenoptera: Crabronidae: Crabroninae) from the Indian subcontinent with the description of three new species from Southern Western Ghats. 468 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 202122 records from National Benthic Inventory. 107 records from Total foraminifera counts from multinet M31/2_MSN890. 16 records from Phenological Center - Fishes (Murmansk). 1057 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 2713 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 1 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 45 records from Estimated plankton abundance at station PS63/064-6. 1070 records from CNAN/Araneae. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 88 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 177 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 527 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 1091 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1359 records from GEO Biodiversity Day. 351778 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 28 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 24 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 922 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 3979 records from Colección de Zoología Invertebrados - Helmintología. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 223486 records from Phytochorologie des départements français. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 186 records from Benthic foraminifera and algae abundance of Hole 81-554. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 105 records from Conocimiento integral del tapir (Tapirus bairdii) y el pecari de labios blancos (Tayassu pecari) en México. 25498 records from fishes_inep_and_nfh. 89 records from Total foraminifera counts of multinet POS247/2_MSN1384. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 244406 records from Carnet B Lorraine. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 256 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 101 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 321633 records from Seasearch Marine Surveys in England. 38 records from Planktic foraminifera abundance of Hole 84-566C. 21 records from The Resin and Carder bees of south India (Hymenoptera: Megachilidae: Anthidiini). 227 records from A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea. 75 records from Naturpark Kottenforst-Ville 19.6.09. 228 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 14009 records from Collection Trichoptera - SMF. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 3 records from Contribution to the knowledge of the genus Visiana Swinhoe (Lepidoptera: Geometridae: Larentiinae), with the description of two new species from Indonesia. 62 records from Genotipificación de especies de la ictiofauna del Sistema Pánuco-Tamesí a través de la generación del código de barras de ADN mitocondrial. 18900 records from UCBG TAPIR Provider. 196 records from Collection des mammifères d'Auvergne. 12 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 483 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 48 records from Morphologische Daten von Natrix. 12699 records from Soil metagenome from healthy and unhealthy agricultural soil. 12645 records from Brown University Herbarium. 118 records from Collection botanique Lamy de la Chapelle E. (BOUM). 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 89 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 98 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 9 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 728 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 1217 records from 16S rRNA metagenomic investigation of arsenotrophic bacteriome of ground water and soil from arsenic-prone area of Bangladesh. 14 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 140 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 8 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 201 records from Biodiversity of springs and rock seepages 2003. 1 records from The Indian net-casting spider name Deinopis goalparaensis Tikader & Malhotra is a nomen dubium (Araneae: Deinopidae). 10777 records from CEFS_16S_ITS. 1268 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 101 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 42 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 521 records from Schanzenanlage Bergham. 140 records from Planktic foraminifera abundance of Hole 37-332. 2 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 10 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 1862 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 98 records from Total foraminifera counts of multinet POS231/3_MSN1332. 906 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 7 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 561 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 603 records from Nannofossil abundance of Hole 37-334. 4 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 59 records from Schulgelände SGD/Viersen. 42 records from Flies from L.A., The Sequel: A further twelve new species of Megaselia (Diptera: Phoridae) from the BioSCAN Project in Los Angeles (California, USA). 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 1 records from Zur Kenntnis der Lithobiiden. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 1049 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): range chart in percentages of calcareous nannofossils. 279 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 3 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 224 records from Natura 2000 PnrL. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 205 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 22 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 8 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 2498 records from Helmintos parásitos de peces del sureste de México. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 2 records from A new pseudoscorpion genus from western Georgia (Pseudoscorpiones: Neobisiidae: Cornuroncus n. gen.), with a key to all Neobisiinae genera. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 4 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 215 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 16 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 353 records from Données naturalistes de Hubert GUIMIER. 1728 records from Collection rousset -1947-2013. 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 177 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 154 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 1 records from Schulman's Neotropical Adelobotrys database. 12094 records from Amino acid addition experiment Metagenome. 26 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 39345 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 21 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9349 records from Harriet Irving Botanical Gardens (HIBG). 46580 records from Weed and native flora data for the Swan Coastal Plain. 99 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1941 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3078 records from Insectes Hyménoptères Scollidés de France. 3 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 1345 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 916 records from IOW Natural History & Archaeological Society Marine Records. 17 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 7527 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 14 records from Occurrence of mammalia relicts at site Climauti II. 142 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 135 records from Waldi-Weiher. 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 4 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 6441 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 51 records from Visual Plants (144.41.33.158) - Private collection of Asta Napp-Zinn. 80 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 3340 records from Palaeobiology collection, FAU Erlangen. 38 records from Phytoplankton counted on two fractions of surface sediment samples from stations B-5 to B-47. 30 records from Planktic foraminifera abundance of Hole 14-144. 3102 records from seawater metagenome Metagenome. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 364 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 4372 records from Heliconiine Butterfly Collection Records from University of Cambridge. 800 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 255 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 79 records from Birdrace-Bielefinken-Bielefeld. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 61798 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 134 records from BIRDRACE Griffin Wood Warblers. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 15 records from Nannofossil abundance of Hole 10-93. 140 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 2 records from Porifera ZMK. 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 4 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 263 records from Planktic foraminifera counts of sediment core V14-77. 10 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 3800 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 76 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 2476 records from Range table from benthic foraminifers in ODP Hole 154-929A. 389 records from Amphibian and Reptilian (KIEE-AR). 1285805 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature). 413272 records from DATAVES. 41 records from Planktic foraminifera counts of sediment core V28-128. 44348 records from Heterogeneity of methane seep microbiomes in the NE Pacific. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 2 records from Bioacoustics review of Anatolian species of the predatory bush-cricket genus Saga (Orthoptera: Tettigoniidae: Saginae) with the description of a new species. 265 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 7 records from Planktic foraminifera abundance of Hole 53-418B. 24283 records from Berea College, Ralph L. Thompson Herbarium. 167 records from Nannofossil abundance of Hole 7-62A. 3592 records from Amphibiens de Guyane. 424 records from Distribution of nanoplankton at trap WR2. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 11 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 30 records from Nannofossil abundance of Hole 9-82. 50 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 91253 records from CUMV Fish Collection. 7 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 931 records from South American Antarctic Marine Biodiversity Literature. 6922 records from MUST, Insecta. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 637398 records from Données ONF Faune-Flore-Fonge. 57 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 2116 records from Collection entomologique Pierre Lachiver. 49 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 50 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 48 records from Deutsche Schule Budapest. 22 records from Thirteen new records of ferns from Brazil. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 435 records from Marine metagenome ICM_AWP. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 202392 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 164768 records from University of Michigan Museum of Zoology, Division of Mollusks. 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 121 records from Foraminifera abundance of sediment core IN68-28. 43 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 5 records from Occurrence of mammalia relicts at site Siebenlinden 3. 122 records from M. Burton (1936). The Fishery grounds near Alexandria IX – Sponges. Notes and Memoirs No.17. Department of Zoology, British Museum. Fisheries Research Directorate. Ministry of Commerce and Industry, Egypt.. 152 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 3 records from Review of the fossil record of Bittacomorphinae (Diptera: Ptychopteridae). 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 319 records from Range table from benthic foraminifers in ODP Hole 144-874B. 613 records from Données acquises via le réseau du CBNBP. 2340 records from Type Specimen Database of Museum and Institute of Zoology PAS. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 6336 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 62161 records from DASSH Data Archive Centre Academic Surveys. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 558 records from Foraminifera abundance of Hole 74-526A. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 9 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 513 records from Quoll sightings register for Nth QLD. 55 records from Highland biodiversity of Fanniidae (Insecta, Diptera): fourteen new species from the Andes and Central America. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 6 records from Alburnus magnificus, a new species of bleak from the Orontes River drainage (Teleostei: Leuciscidae). 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 8 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 237 records from Planktic foraminifera abundance of Hole 21-207. 11 records from Données naturalistes de Thibault RAMAGE. 12 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 16 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 608 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 43 records from Vogelstimmenführung durch den Tiergarten. 41618 records from Données naturalistes de Pierre JAY-ROBERT. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 84 records from Ostracoda abundance of Hole 48-403. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 13 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 7 records from Three new species of the genus Mimetus Hentz, 1832 (Araneae: Mimetidae) from Yunnan-Guizhou Plateau of China. 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 35 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 51113 records from Atlas des Orthoptères et Mantides de France métropolitaine. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 1418 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 15757 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 2 records from Description of Metarhabditis giennensis sp. n. (Nematoda, Rhabditida, Rhabditidae) from decaying wood of a riverbank forest in the southern Iberian Peninsula. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 24 records from Ostracoda abundance of Hole 48-406. 771 records from GEOECOLINK_2017_12_18. 16 records from Hazel Dormouse in Ireland. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 1698 records from UTEP Herpetology Osteology (Arctos). 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 85255 records from The Scottish Squirrel Database. 2 records from Revision of the tree crickets of China (Orthoptera: Gryllidae: Oecanthinae). 3 records from New Earwigs in Protodiplatyidae (Insecta: Dermaptera) from the Middle Jurassic Jiulongshan Formation of Northeastern China. 285 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 11 records from Tanytarsini (Diptera: Chironomidae) from madicolous habitat in Southeast Brazil: new species and new records. 46 records from Planktic foraminifera counts of sediment core V26-124. 13 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 36 records from Selz (Ingelheim am Rhein). 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 398 records from Tsetse flies of East Africa update. 123 records from Total foraminifera counts of multinet M21/4_MSN694. 4 records from A new species of Heliothrips (Thysanoptera, Panchaetothripinae), based on morphological and molecular data. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 88 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 52443 records from Extracellular DNA marine sediment Targeted Locus (Loci). 1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 5 records from Microfossil abundance of Hole 21-208. 217 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 928 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 1 records from Occurrence of mammalia relicts at site Ejstrup. 2340 records from marine metagenome Targeted Locus (Loci). 28385 records from Plan de vertebrados de la Patagonia. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 67 records from Planktic foraminifera distribution of sediment core TRI171-27. 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 3 records from Occurrence of mammalia relicts at site Igstadt I. 268 records from Planktic foraminifera abundance of Hole 22-217. 2 records from Myzostoma khanhkhoaensis (Myzostomida), a new myzostomid species from the Nhatrang Bay, Vietnam. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 8 records from Nannofossil abundance of Hole 39-353A. 16988 records from LPO_PACA_2017_12_18. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 232661 records from Oklahoma Vascular Plants Database Provider. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 6556 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 41553 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 28439 records from Collection Pisces SMF. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 1642 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 442 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 242 records from Landschaftspflegehof (Berlin). 84 records from Total foraminifera counts from M35/1_MSN1051. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 91 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 2917 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 17 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 251297 records from Estonian Nature Observations Database. 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1095 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 17713 records from NCSM Mammals Collection. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 770 records from Nivå Bay species list, Zealand, Denmark. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 814 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 96290 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 164135 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 151 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 7814 records from Odonata de Veracruz. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 3797 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10484 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 16506 records from Database for alien invasive plants occurrences in Germany. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 871 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 533 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 10212 records from Spider (NSMK-SP). 27947 records from OUPR - Herbário "Professor José Badini". 15 records from Nannofossil abundance of Hole 58-442B. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 12418 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 56 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 125 records from Range table from ostracoda in ODP Hole 143-866B. 7446 records from Fish specimens of Toyama Science Museum. 6004 records from Colección Limnológica Universidad de Antioquia. 3 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 181857 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 3529 records from A dataset from bottom trawl survey around Taiwan. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 11 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 2 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 27108 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 210 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 14 records from (Table 4b) Biomass of Emiliania huxleyi and its role in total biomass of phytoplankton along the section from the Pribilofs Islands to the Nunivak Island on 24-25 August 2001. 30008 records from Lepidoptera specimen database of Japan. 308173 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 43 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 130 records from BIRDRACE - The famous Grouse feat. The James. 374 records from Planktic foraminifera abundance of Hole 68-503B. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 45 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Helmut Dalitz. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 552 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 4 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 31 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 52 records from Occurrence of mammalia relicts at site Goyet Cave 3. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 36 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 515 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 81329 records from natagora-earlybirds. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 18 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 35 records from Reptiles Specimens of Akita Prefectural Museum. 339 records from UWIZM Snakes. 10552 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 1 records from Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae). 182 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 2421 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Tanacetum vulgare dominated forb vegetation. 7471 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 4 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 7791 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 4585 records from Marine bacteria Targeted Locus (Loci). 292 records from Atlantic Forestry Centre Insect Reference Collection. 2136 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 55 records from Occurrence of mammalia relicts at site Rusenschloß. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 98 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1215 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 1663 records from Marine eukaryotes Targeted loci environmental. 15 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 276 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 2980 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 675 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1477 records from Oxygen minimal zone Targeted loci environmental. 72399 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 15647 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 7 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 2 records from Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate. 14 records from Lane 6 Analysis. 3939 records from Census of plant species in Pahou forest reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 1 records from The taxonomic implication of frontal tubercles in Polypedilum subgenera diagnoses, with re-description of Polypedilum isigabeceum Sasa & Suzuki (Diptera, Chironomidae). 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 7462 records from Ibaraki Nature Museum, Fungi collection. 924 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 190 records from Relative abundance of ostracods in sediment core Sv09. 384 records from Saltern microbial community diversity. 209 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 181977 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 32 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 48 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 323 records from Size of planktic foraminifera at CTD station PS55/083-1. 312 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 34103 records from R. L. McGregor Herbarium Lichen Collection. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 1165 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 557 records from Corn bunting breeding distribution in Scotland. 3171 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 69 records from Foraminifera species abundances from tow TT007_7-MOC13. 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 33 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 6 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 9329 records from Centre de Ressources Biologiques de l'Institut Pasteur. 40798 records from Banded Iron Formation and Greenstone survey data. 28 records from Microzooplankton abundance and biomass at station TT045_19-3. 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 3 records from Description of Walkeriella miraculosa, gen. n. et sp. n. from South-East Peru (Lepidoptera: Hepialoidea: Hepialidae). 3 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 131 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 53 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 30 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 6 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 3 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 1900 records from Fungi Collection. 5 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 4 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 40281 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 179 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 120 records from Total foraminifera counts of multinet M10/2_MSN262. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 20 records from Description of lithologic section units of IODP Hole 325-M0033A. 46 records from An der Ohm, (Wettsaasen). 8 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 49 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 3 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 20755 records from pins. 1005 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 2419 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 91 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 701 records from Range table from benthic foraminifers in ODP Hole 151-913B. 40 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 2177 records from SMNS Palaeontological collection - Invertebrates (Cenozoic). 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 1985 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 31457 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 124 records from Kirkliston Range stream monitoring. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 25446 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 12 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 5538 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 5314 records from Dados da ocorrência de plantas lenhosas em um gradiente de perturbação/precipitação em área de Caatinga, Parque Nacional do Catimbau, Buíque, PE, Brasil. 11129 records from Royal Ontario Museum Fungarium (TRTC). 4686 records from Butterfly_conservation_2017_12_18. 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 137398 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 96 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 34224 records from Données bibliographiques et opportunistes Odonates issues du SiRF. 19 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 3429 records from Mise en place d'un suivi scientifique des amphibiens pour la production d’indicateurs de biodiversité. 547 records from Metagenome microbial communities of bottom sediments of the Kara Sea. 6 records from Taxonomic status of the barbastelles (Chiroptera: Vespertilionidae: Barbastella) from the Japanese archipelago and Kunashir Island. 99 records from Düne am Ulvenberg (Darmstadt). 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 345 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 2656 records from Swiss Psyllid (Hemiptera) Collections - Basel. 45 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from Spockia tagala gen. and sp. nov. a new monotypic genus of Asopinae (Hemiptera: Heteroptera: Pentatomidae) from the Philippines. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 537 records from Pilotovervåking av dragehode Dracocephalum ruyschiana. 1059 records from Planktic foraminifera abundance of Hole 15-148. 12127 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 258 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 28 records from Korean Plant Virus Database. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 14 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 29 records from Herbarium Senckenbergianum (FR) - Protista. 3 records from Zoology in the Middle East. 6446 records from Modernisation des ZNIEFF du PnrL. 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 20 records from Occurrence of mammalia relicts at site Niederlehme. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 86 records from UWIZM Cnidarians. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 152253 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40344 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 28 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1001 records from Mushroom (KIDR-MR). 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4579 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 887 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Occurrence of mammalia relicts at site High Furlong. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 2648 records from University of Sindh Jamshoro Herbarium. 2924 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 1140 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 128 records from Faunal assemblage of sediment core TR149-32. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 1 records from Hoplophora ardua. 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 111 records from Birdrace-Uhulogen-Lippe. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 7128 records from La familia Asclepiadaceae en México. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 373 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 43 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 411 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 597 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 61 records from Alien Species in Poland - Plants. 39139 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 64 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 14853 records from Données bibliographiques et opportunistes Mammifères issues du SiRF. 638313 records from Données de la flore d’Alsace (SBA). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 1153 records from Nannofossil abundance of Hole 17-167. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 284 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 289 records from bmhs_butterfly_collection. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 3817 records from Microbial communities associated with ferromanganese nodules and the surrounding sediments. 3 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 172 records from checklist-of-birds-of-zomba-mountain. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 110866 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1694 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 61942 records from EAC - Herbário Prisco Bezerra. 2565 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 247 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 30260 records from Collection Crustacea - ZMB. 742 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 212 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 109 records from MMFR Zingiberaceae Botanical. 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 31 records from Nannofossil abundance of Hole 9-82. 2660 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 2327 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 114 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 153 records from Planktic foraminifera abundance of Hole 18-181. 22167 records from Natural History Museum Maastricht (NL) - Herbarium. 9404 records from MZL Invertebrate Collections. 1303 records from Crustacean specimens of Bihoro Museum. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 64 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 170 records from Total foraminifera counts of multinet SO117_MSN1244. 8956 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 9 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 5619 records from uncultured prokaryote Targeted loci environmental. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 3435 records from Benthos Chirnov Basin 1986 and 2002. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 51 records from Coccoliths in sediment core GIK23065-3. 1 records from Neotropical Monogenoidea. 60. Two new species of Gyrodactylus (Monogenoidea: Gyrodactylidae) from the armored-catfish, Pareiorhaphis parmula Pereira (Loricariidae) and from the cascarudo, Callichthys callichthys (Linnaeus) (Callichthyidae) from Brazil. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 251 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 1004 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 10 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 26159 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 12 records from Analyses of the recent components of sediment core PS1219-1. 44802 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 339 records from HBRG Invasive Non-native Plants Dataset. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 6 records from Pushing the limits - two new species of Pteromalus (Hymenoptera, Chalcidoidea, Pteromalidae) from Central Europe with remarkable morphology. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 6 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 203916 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 21884 records from Birds Specimens. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 56 records from Planktic foraminifera abundance of Hole 23-227. 19164 records from DMNS Mammal Collection (Arctos). 43 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 6 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 1519 records from IBF Monitoring of Fungi. 5 records from Cryptic species among bumblebee mimics: an unrecognized Hemaris hawkmoth (Lepidoptera: Sphingidae) in eastern North America. 15 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 2242 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 1809 records from BenthosChukchiFN762_1976_Falk5. 1054 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 104 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 254 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 53 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 5000 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 240 records from Knechtweide (Kohlfurth). 18 records from Benthic macrofauna abundance of sediment core 12930-073. 1584 records from MCP-Mamiferos - Coleção de Mamíferos. 582 records from Stable isotope data and sedimentology of core SO42-74KL. 89 records from Meniscus Midges (Dixidae) of Ireland. 73 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 1757 records from Occurrence database of native plants and animals of south-central Chile. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 26 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 282 records from Deponie Klausdorf. 48 records from Schulgelände (Wetter). 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 61 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 22817 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1986 records from Données Cetonidae -1981-2014-LACOSTE Frédéric. 61 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 31 records from Benthic foraminifera abundance of Hole 42-379A. 1489 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipaility – Norway; 1996 – 2017 based on systematic catches with ordinary mouse traps in traplines. 1376 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 2548 records from BioGIS - Reptiles - HUJ collections. 10 records from Analyses of the recent components of sediment core PS1222-1. 768971 records from Flora Atlas N.T.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 54 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 1597 records from Herbario COFC de la Universidad de Córdoba: colección histórica. 10 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 8 records from A new species of Phonotimpus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) from Mexico. 1191 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 10 records from Ostracoda abundance of Hole 32-306. 630 records from Nannofossil abundance of Hole 29-281. 8069 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 315 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 13 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 580 records from Rare plants database extract from Scottish Natural Heritage. 68396 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27264 records from Formidabel; Belgian Ants Database. 2 records from A new species of Globicornis Latreille (Coleoptera: Dermestidae) from Baltic amber, with a key to fossil species. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 126 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 1 records from A new African Apiocera species (Apioceridae, Diptera). 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 5978 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 1271 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 127 records from Сypripedium guttatum Sw. in the Komi republic. 148 records from Abundance of birds in the Lena Delta Region. 8 records from Ascidians collected during the Madibenthos expedition in Martinique: 2. Stolidobranchia, Styelidae. 79 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 32 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 1 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 35 records from Ortsrand Zandershagen. 39 records from Planktic foraminifera counts of sediment core V19-21. 9150 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 2952 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 2 records from A new African species of Stenichnodes (Coleoptera: Staphylinidae: Scydmaeninae). 40 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 180 records from Données naturalistes de Pascal Dupont. 130 records from Faunal assemblage of sediment core GS7603-13. 437 records from Bird specimens of Bihoro Museum. 2 records from Wie viel Natur gibt es im Park?. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 5515 records from Colección de Anfibios. 11143 records from NBMB Herps. 386 records from Foraminifera distribution of sediment core KS310. 5979 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 138 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 102 records from (Table 3) Abundance and biomass of Proboscia alata in patches of its mass development over the Bering Sea middle shelf, percentages of P. alata and associated algae species and their groups in total phytoplankton abundance and biomass. 70 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 59 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 5 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 211452 records from University of Michigan Museum of Zoology, Division of Birds. 7 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 2645 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 623 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 6 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 363 records from (App 1) Relative contents of mass species of benthic foraminifera in Holocene sediments from Core ASV11-880-3. 1000 records from Collection Graptolithina fossil SMF. 11 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 82649 records from Specimen Database of Colorado Vascular Plants. 25953 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 12 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 62 records from Zoo Frankfurt. 212 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 1085628 records from Fungal Records Database of Britain and Ireland. 1112 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 61999 records from La familia Asteraceae en México. Fase VI. 610 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 2312 records from Mycological collection of the National Museum. 63 records from Marine gastropod distribution from patagonian shallow waters. 6 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 21 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 9 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 1 records from Two new species of obligatory termitophilous rove beetles from Brazil (Coleoptera: Staphylinidae: Termitomorpha Wasmann). 203 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 8 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 16 records from Dinoflagellate cysts of surface sediments. 7 records from Collection Malakologie - SMNG. 47 records from Données d'observation de phanérogames marines en Martinique. 1721 records from Phytoplankton data collected from the Black Sea during November 1957 (Cruise 2). 374 records from Coastal and Marine Species Database. 190 records from Nannofossil abundance of Hole 67-499. 6 records from A new species of Tambitnotia from Peru, with the first reported female of the genus (Lepidoptera: Tortricidae: Olethreutinae). 587 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 1 records from Description of females of Chilarboreus Ruta, 2011 (Coleoptera: Scirtidae: Scirtinae). 401 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 6083 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 242 records from UTEP Fish (Arctos). 7 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 383 records from Nannofossil abundance of Hole 66-490. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 270 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 1136 records from Nannofossil abundance of Hole 82-558A. 3327 records from BioGIS - Mammals - SPNI. 91840 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 23 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 216 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 141 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 77414 records from MfN - Fossil vertebrates IV. 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 46118 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3439 records from MEXU/Flora de Oaxaca. 1 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 287 records from Nannofossil abundance of Hole 66-488. 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 9304 records from Echinoderm collection of National Museum of Nature and Science. 109176 records from Herps Specimens. 1450 records from Données naturalistes d'Alain BERLY. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 125351 records from Dataflos. 26 records from Halocosa gen. n., a new genus of Lycosidae (Araneae) from the Palaearctic, with a redescription of H. cereipes (L. Koch, 1878). 175 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 2746 records from marine sediment metagenome Raw sequence reads. 34 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 1066 records from Territorial Andes Occidentales - Densidad poblacional VOC subsistema cámaras trampa, 2018. 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 2 records from A new subspecies of Zamenis hohenackeri (Strauch, 1873) (Serpentes: Colubridae) based on morphological and molecular data. 4031 records from Benthic foraminifera distribution of sediment core GIK17957-2. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 4 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 1000 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 621 records from BID-Malawi-Geometridae-Biodiversity-Data. 190 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 46 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 15968 records from JOI - Herbário Joinvillea. 31 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 10 records from Four new species of the subgenus Pachylaelaps (Longipachylaelaps) from Italy, with a new identification key to the known species (Acari: Pachylaelapidae). 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 81 records from Birdrace-Die_Ornithomaten-Herford. 5 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 3 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 2360 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 103 records from Mammals (UWEP-MM). 84981 records from NINA Vanndata fisk. 31 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 510 records from Inventaires des cygnes du département de l'Eure. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 53062 records from British Antarctic Survey Argos satellite tracking data. 1 records from Zetes pallidulus. 1 records from A new jellynose, Ateleopus edentatus, from the western Pacific Ocean (Teleostei: Ateleopodiformes: Ateleopodidae). 3 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 114 records from Total foraminifera counts of multinet M26/1_MSN844. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 14 records from Taiwanese deep-water chitons (Mollusca: Polyplacophora) and survey of chiton fauna of Taiwan. 5 records from Nesting biology of Paragymnomerus signaticollis tauricus (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae). 3415 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 5 records from On some species of the genus Acrolocha Thomson, 1858 of the Western Palaearctic Region (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 29646 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 10 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 836 records from Odoanta of Akwa Ibom State University, Nigeria. 1197 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 197 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 12761 records from Données naturalistes de Franck NOEL. 343 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 2 records from Tamdamaeus staryi gen. nov., sp. nov. (Acari, Oribatida, Damaeidae) from Vietnam, with remarks on certain unusual diagnostic features. 2369 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 7 records from Revision of Sinonereis Wu & Sun, 1979 (Annelida: Nereididae). 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 120 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 119365 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 13 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-104BX. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 448 records from Harpactus Shuckard. 2500 records from Los crustáceos decápodos marinos: Actualización de la colección carcinológica de la Facultad de Ciencias Biológicas, UANL. 41 records from List of Snail species in Vava'u. 2 records from A new species of freshwater crab of the genus Strengeriana Pretzmann, 1971, from El Jardín Natural Reserve, Quindío, Colombia (Crustacea: Decapoda: Pseudothelphusidae). 3 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 381 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 5 records from Open-holed trapdoor spiders of the genus Teyl (Mygalomorphae: Nemesiidae Anamini) from Western Australia’s Pilbara bioregion: a new species and expanded phylogenetic assessment. 11194 records from Baselines Initiative 16S rRNA gene dataset: Baselines Amplicon Release 1 (R1) Caribbean Sea near Curacao (including saline pond samples in Curacao) 2015. 2974 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 14590 records from SMNS Palaeontological collection - Invertebrates (Jurassic and Cretaceous). 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 3 records from Two new species of the Simulium (Simulium) tuberosum species-group (Diptera: Simuliidae) from Palawan, the Philippines. 88 records from "Schlechteberg" Ebersbach/Sa.. 9519 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 4484 records from (Table 1) Occurrence of selected planktonic foraminifers, other microfossils, and lithologic components at DSDP Hole 96-619. 2 records from Anophtalmic and epigean? Description of an intriguing new species of Hyalella (Amphipoda, Hyalellidae) from Brazil. 2 records from Three new species of Synagelides Strand, 1906 from China (Araneae: Salticidae). 136 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1371. 42 records from Nannofossil abundance of Hole 1-3. 89 records from A Synopsis of the Odonata (Dragonflies) of Sumatra. 611 records from Planktic foraminifera counts of sediment core V29-64. 27351 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 193 records from Loup 2009 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 11253 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 2427 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 2 records from A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic. 1 records from Arthropoden aus südostalpinen Höhlen.. 224 records from Phytoplankton abundance during Arne Tiselius cruise AT91/2. 536 records from Kieppi bird collection. 439 records from Revision of Chondrocyclus s. l. (Mollusca: Cyclophoridae), with description of a new genus and twelve new species. 1296 records from Plant specimens of the Museum of Yamagata University. 55 records from SNH Invertebrate Site Condition Monitoring 2015: Rinns of Islay SSSI. 20945 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 18 records from Biodiversidad en el valle de Cuatro Ciénegas.. 17 records from Peces de la expedición en el páramo El Consuelo, Boyacá - Proyecto Boyacá BIO. 113 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 139730 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 1 records from Thismia nigricoronata, a new species of Burmanniaceae (Thismieae, Dioscoreales) from Vang Vieng, Vientiane Province, Laos, and a key to subgeneric classification. 180 records from (Table 7) Distribution of the large, many-chambered Globigerinelloides species in DSDP Hole 79-545. 3 records from Two new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from Thailand. 32266 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 3 records from A new Paramathes Boursin, 1954 (Lepidoptera, Noctuidae) species from China. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 107 records from A synopsis of the genus Dorcasta Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini). 366 records from Climate Change Adaptation Research Program (CCARP) Database of Watering Requirements - Images. 16540 records from Inventaire des Mammifères marins de France (métropole et outre-mer). 1 records from A new species and key to all known species of Confusacris Yin & Li, 1987 (Orthoptera: Acrididae) from China. 11 records from Two new genera of pyroglyphid mites, Tuccioglyphus and Marioglyphus, with a key to genera of the World (Acari: Pyroglyphidae). 211 records from Stadt Königs Wusterhausen. 1957 records from BioGIS - Marine snails - HUJ collections. 111 records from Ökologischer Weinberg (Guntersblum). 23774 records from Molluscus specimens of Toyohashi Museum of Natural History. 50902 records from Anfibios y reptiles de las regiones 30 (Parque Natural Sierra Maderas del Carmen); 31 (Sierra El Burro-Río San Rodrigo); 36 (Sierra La Encantada); y 37 (Sierra El Pino), Coahuila. 43 records from Two new species of Ecpatia Turner, 1902, and the first records of Ecpatia sciachroa Hampson, 1926 and Ecpatia obscura Holloway, 2009 from Thailand (Lepidoptera: Noctuidae, Noctuinae). 48 records from Ruhrwiesen bei Neheim-Hüsten. 7 records from Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae).. 293 records from Macrofauna, entomofauna y vegetación vascular de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 9 records from New taxa of pygmephoroid mites (Acari: Pygmephoroidea: Pygmephoridae, Neopygmephoridae) phoretic on Enoplotrupes sharpi (Coleoptera: Geotrupidae) from Thailand. 120 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-14. 271 records from ABC Matandwe Forest Reserve Vegetation Survey. 50095 records from Fungi of Costa Rica (INBio). 169627 records from Intermountain Herbarium (Utah State University). 48 records from Planktic foraminifera abundance of Hole 25-241. 2010 records from Microbial community structure of chronically polluted marine sediments from a cold region of the southern hemisphere. 91356 records from 臺灣兩棲類資源調查與教育宣導推廣計畫 Resources survey and education advocacy to promote for Taiwan amphibian resources. 2420 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 5361 records from Colección Ornitológica de la Universidad del Valle. 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 4 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 77 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 207 records from Données de Mammifères marins. Mission AGOA de 2012 à 2014. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 324 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 8 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 172 records from Total foraminifera counts from multinet M31/3_MSN915. 975046 records from NatureServe Network Species Occurrence Data. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 41676 records from Tagged Seal Location Data from SOGLOBEC. 333 records from Données naturalistes de Renaud PUISSAUVE. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 881 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 4 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1709 records from The Gibson spider collection. 67 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 1256 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 651 records from Réseaux écologiques/Trame verte et bleue. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 14 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 66164 records from Florida Keys Reef Visual Census 1996. 2867 records from Pollichia Pilzherbar. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 24387 records from Données de Luc BARBARO. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 1450 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 874 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 48 records from Total foraminifera counts of multinet M6/7_MSN140. 9810 records from Royal British Columbia Museum Entomology Collection. 106 records from Dinoflagellate abundance of Hole 81-552. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 29 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 477 records from (Table 1) Stable isotope ratios of foraminifera in sediment core CH82-20. 2800 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 5940 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 145 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 1047 records from NZCS Invertebrates New Collection After 1987. 3005 records from Colección Entomológica CDMB. 16933 records from Lepidoptera (Specimens NRM). 2 records from Waidelotinae, a new subfamily of Pyrochroidae (Coleoptera: Tenebrionoidea) from Baltic amber of the Sambian peninsula and the interpretation of Sambian amber stratigraphy, age and location. 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 1644 records from Las comunidades de myxomicetes de selva baja caducifolia. 27810 records from Collection of saproxylic and xylobiont Beetles. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 22586 records from Tachinid Recording Scheme - GB and Ireland records. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 27 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 4617 records from Données de type contact de Guadeloupe. 14566 records from Canadian Museum of Nature Palynology Collection. 89 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 130 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 36 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 2 records from Osteology and relationships of Libanopycnodus wenzi gen. et sp. nov. and Sigmapycnodus giganteus gen. et sp. nov. (Pycnodontiformes) from the Late Cretaceous of Lebanon. 55 records from Galls on Beech Trees in Hainich, 2008. 8 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 9 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 31788 records from Observatoire de la Biodiversité des Jardins (OBJ). 2289 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 6 records from Description of a new Episemion species (Cyprinodontiformes: Nothobranchiidae) from northern Gabon and southeastern Equatorial Guinea.. 648 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 562 records from Pollen analysis of sediment core GeoB6518-1. 494248 records from BLS Mapping Scheme dataset, 1750-2009. 1114 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 34 records from Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae). 53 records from Relative abundance of planktic foraminifera in sediment core K11. 30 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 697 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 1 records from Planktic foraminifera abundance of Hole 54-420A. 40135 records from DIBA-Parc del Montnegre i el Corredor. 22 records from Caracterización de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y Áreas aledañas: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 4764 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 3 records from Re-description of Grammapsychops lebedevi Martynova, 1954 (Neuroptera: Psychopsidae) with notes on the Late Cretaceous psychopsoids. 17 records from Description of lithologic section units of IODP Hole 325-M0043A. 7 records from Grundwasserlebensraum im Englischen Garten (München). 146 records from Cepario de Microorganismos y Hongos Filamentosos de la Universidad del Valle RNC:102. 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 209 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 1576 records from (Appendix B) Nannofossil abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 184 records from Kystfuruskoger 2015. 3 records from On a new marine podocopid genus and species (Ostracoda: Hemicytheridae) from Brazil. 14 records from A new species of freshwater crab of the genus Himalayapotamon Pretzmann, 1966 (Decapoda, Brachyura: Potamidae: Potaminae) from Uttarakhand, northern India. 670 records from Project for Reef Fish Monitoring. 19198 records from FBIP:IZIKO-UCT:Historical Survey (1930-1980). 119 records from COA Egg Collection (Arctos). 98 records from An update on the spider genus Hexophthalma (Araneae: Sicariidae) in the Afrotropical region, with descriptions of new species. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 39 records from Macrohongos en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 95051 records from Hymenoptera collection of the Finnish Museum of Natural History. 1098 records from JOIw - Xiloteca Joinvillea. 13 records from Olbiogaster Osten Sacken (Diptera: Anisopodidae) from Mexico, with the description of three new species. 16 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-113BX. 4 records from Black grouse lek survey in Wester Ross and Skye 2009. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 120 records from Flora polínica de las llanuras de Sonora, al sur de Hermosillo. 553 records from Planktic foraminifera abundance of Hole 49-407. 54 records from VFD-H: MIttelgebirgsweide. 309 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE218. 102 records from Microzooplankton abundance measured on water bottle samples at station PS65/587-1. 4312 records from (Table 18) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-593. 30 records from Smear slide analysis on sediment core GeoB4206-1. 23451 records from marine sediment metagenome Targeted loci environmental. 49022 records from Dreal Corse - Base Ogreva. 61 records from A conspectus of the silver-flies (Diptera: Chamaemyiidae) of the Middle East with descriptions of new species of Chamaemyia Meigen and Melanochthiphila Frey, from the Arabian Peninsula. 28 records from Catochini, Strobliellini and Acoenoniini revisited: a taxonomic review of the small tribes of the Micromyinae (Diptera: Cecidomyiidae). 6 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 28936 records from Amphibian Specimens. 66 records from Rhopalocera of Martinique. 48769 records from Flora of the Stołowe Mts.. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 359044 records from Insect (KNAM-IN). 7812 records from Occurrence data of dragonflies available at the National Museums of Kenya's Natural History Collection, Invertebrates Zoology Section.. 84 records from BIRDRACE Bielefinken. 1 records from Synthèse de la Répartition des populations de cerf élaphe en 1985 (réseau Ongulés sauvages ONCFS-FNC-FDC). 44 records from Phytoplankton abundance in surface water in 1997, Ancon, Peru. 2 records from World genera of Mastigitae: review of morphological structures and new ecological data (Coleoptera: Staphylinidae: Scydmaeninae). 18 records from Microzooplankton abundance and biomass at station TT043_7-20. 3 records from A new myrmecophilous mite species of the genus Cosmolaelaps Berlese, 1903 (Acari, Mesostigmata, Laelapidae) from Central Europe (Slovakia). 33 records from Chronicle of Nature - Phenology of Arachnids of Visimsky Nature Biosphere Reserve. 112 records from Caracterización de Flora de la Reserva Forestal Protectora Regional Brisas del Rincón. 2134 records from gas hydrate bearing sediment Raw sequence reads. 143 records from Taxonomic review of Inella and Strobiligera (Gastropoda: Triphoridae) from Brazil. 16 records from A new Ovia species (Araneae, Lycosidae) from Singapore, with the transfer of Pardosa alboannulata Yin et al., 1997. 38 records from Seven new species of the cicada
Keywords: GBIF; biodiversity; species occurrences